Psychological impacts of COVID-19 on Vietnamese health workers over the prolonged restricted COVID-19 responses: a cross-sectional study - Melvyn W B Zhang; Carl A Latkin; Pascal Auquier; Giang Thu Vu; Roger C M Ho; Cyrus SH Ho; Laurent Boyer; Bach Tran; Minh Trong Nguyen; Guillaume Fond; Thao Phuong Hoang; Phuong Thu Ho; et al. (BMJ Open)
Objective We assessed the psychological impact posed by COVID-19 and its associated factors on the healthcare workforce nationwide during the peak of Vietnam’s fourth outbreak.Design A cross-sectional study.Setting Our study was conducted in 61 provinces of Vietnam.Methods A total of 2814 healthcare professionals in 61/63 provinces of Vietnam. An online questionnaire using Patient Health Questionnaire-9 (PHQ-9), Perceived Stress Scale-4 (PSS-4) and Generalised Anxiety Disorder-7 (GAD-7) scales was distributed randomly to a subgroup of 503 respondents.Primary and secondary outcome measures To determine the impact of COVID-19 on the psychological of health workers, we conducted analyses to test a primary hypothesis related to participants based on three main scales including PHQ-9, PSS-4 and GAD-7 scales.Results Nearly half (49.7%) of healthcare workers experienced mild depression symptoms, 34.0% underwent moderate anxiety symptoms and 49.3% reported high-stress levels. Respondents who had a monthly income below 5 million VND (~US$212) and had more than 3 days of duty per week had a higher score on the anxiety scales. Compared with medical doctors, nurses/midwives had lower PHQ-9 (Coef=−2.53; 95% CI=−3.71 to −1.36) and GAD-7 scores (Coef=−2.36; 95% CI=−3.56 L to −1.16). Increased workload and work time was the harmful factor that increase the PHQ-9, GAD-7 or PSS-4 scores. More than half (53.9%) of respondents stated no demand for mental healthcare services.Conclusions Health workers who gained less financial rewards are reported to have higher levels of mental distress than others, implying the need for a raise in basic salary as well as compensation and encouragement schemes. To tackle hesitancy in seeking mental help, integrating online mental health therapy with e-health consultations via social media can be strategically implemented to augment service delivery, and simultaneously enhance the standard of mental health services.